Enhancing the assessment of cardiorespiratory fitness using field tests - Marques, Alda (2020)
Objective: To establish normative values and reference equations of the 6-minute walk test (6MWT), incremental shuttle walk test (ISWT) and unsupported upper limb exercise test (UULEX) for Portuguese adults. Design: Cross-sectional study. Descriptive statistics and differences between age decades and genders were explored using univariate general linear models to compute reference values. Reference equations were established with a forward stepwise multiple regression. Setting: General community. Participants: In total, 645 adult volunteers without disabilities [43% male, mean age 55.1 (standard deviation 23.6) years] were recruited from the university campus and surrounding community. Intervention: Not applicable. Main outcome measures: Data on age, gender, height, weight, body mass index and smoking status were collected using a structured questionnaire. Physical activity was evaluated using the Brief Physical Activity Assessment Tool. Participants performed two repetitions of the 6MWT, ISWT and UULEX, and the best repetition was used for analysis. Results: Overall, performance was better in males than in females, and decreased with age. Participants’ performance was significantly reduced after the sixth decade of life compared with the other decades (P < 0.001). Reference equations were: 6MWT = 226.93 − (5.00 × age) + (360.41 × height), R2 = 71%; ISWT = 393.81 − (17.98 × age) + (185.64 × gender) + (775.88 × height), R2 = 83%; and UULEX = 16.71 − (0.14 × age) + (2.66 × gender), R2 = 57%. Conclusion: Leg or arm exercise field tests are affected significantly by age and gender. These results will aid health professionals to interpret the results of field tests obtained from healthy or diseased adult populations.